Morphological and physiological differences in the upper trapezius muscle in patients with work-related trapezius myalgia compared to healthy controls: A systematic review. (June 2017) - De Meulemeester, Kayleigh; Calders, Patrick; De Pauw, Robby; Grymonpon, Ine; Govaerts, Anke; Cagnie, Barbara
Abstract: Background: Trapezius myalgia is a common musculoskeletal complaint, characterized by pain, stiffness and tightness of the upper trapezius muscle. It is often work-related and caused by prolonged static and repetitive work tasks. It is hypothesized that this leads to various morphological and physiological alterations in muscle tissue but the pathophysiology is poorly understood. These alterations can be investigated by analysing muscle biopsies in order to reveal the underlying cellular mechanisms. Objectives: This systematic review aimed at providing a summary of the existing literature regarding morphological and physiological differences between people with work-related trapezius myalgia and healthy controls, obtained by analysing muscle biopsies. Design: Systematic review. Methods: A systematic literature search was performed in following databases: Pubmed, Web of Science and Embase by using different keyword combinations. This systematic review is reported following the PRISMA guidelines. Results: Generally, low to moderate evidence was found for the absence of differences in muscle morphology in people with trapezius myalgia, compared to healthy controls. However, significant differences were mainly found in comparison with the control group with another occupation than the myalgic group. It can thus be hypothesized that morphological alterations in muscle tissue are related to work load and not to pain. Low to moderate evidence was also found for the absence of differences at the physiological level. Conclusions: Based on this systematic review, there are no clear differences in muscle morphology and physiology between subjects with trapezius myalgia and healthy controls. Highlights: No clear differences in muscle characteristics between myalgic and healthy subjects. Differences in muscle characteristics seems to be related to work, not to pain. Large variety in the methodology of the included articles.